Prophets, Studio Revolutionaries, and On-the-Ground Activist: Hip-Hop/Rap Artists' Approaches to Community Engagement - Sweet, Castel (2014)
With few exceptions, previous scholarship on rap and hip-hop music focuses on the study of lyrics and videos; emphasizing the negative influence that artists have on their communities and on perpetuating inequality in the United States. Contrarily, this study explores artists’ embeddedness in local communities, their interpretation of the connectedness of their work to their communities, and the impact they have as individual civic actors outside the narrow limits of their art. Using in-depth interviews with self-identified rap and located in the Southern region of the United States, I explore artists’ personal narratives of the social issues that plague their communities and how they address them as artists within the framework of new social movement theory. My findings indicate that rap and hip hop artists see themselves as addressing community issues in two ways: through physical activism within their communities and verbally motivating listeners with their music